2015
DOI: 10.1007/s12032-015-0647-2
|View full text |Cite
|
Sign up to set email alerts
|

Antithymocyte globulin combined with cyclosporine A down-regulates T helper 1 cells by modulating T cell immune response cDNA 7 in aplastic anemia

Abstract: Antithymocyte globulin (ATG) combined with cyclosporine A (CsA) has been widely used as a standard regimen in the treatment of aplastic anemia (AA), especially in severe aplastic anemia (SAA). Abnormally activated T cells might be the immune pathogenesis of AA. T cell immune response cDNA 7 (TIRC7) has been demonstrated its essential role in T cell activation; however, little is known about the role of TIRC7 in AA. In this study, we documented that TIRC7 levels in CsA group were higher than that in ATG + CsA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Meanwhile, our previous study also found that CTLA-4 levels were decreased in patients with aGVHD before aGVHD treatment (corticosteroids as the first-line standard treatment for II-IV aGVHD) (18), whereas they were increased in patients with aGVHD after treatment (6). However, TIRC7, a novel membrane molecule, has been shown to be an essential molecule in the regulation of lymphocyte activation, and its expression is increased prior to aGVHD treatment (corticosteroids as the first-line standard treatment for II-IV aGVHD) but decreased following treatment (6,18,30). A previous study demonstrated that TIRC7 plays an important regulatory function in both T and B cell responses (19).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, our previous study also found that CTLA-4 levels were decreased in patients with aGVHD before aGVHD treatment (corticosteroids as the first-line standard treatment for II-IV aGVHD) (18), whereas they were increased in patients with aGVHD after treatment (6). However, TIRC7, a novel membrane molecule, has been shown to be an essential molecule in the regulation of lymphocyte activation, and its expression is increased prior to aGVHD treatment (corticosteroids as the first-line standard treatment for II-IV aGVHD) but decreased following treatment (6,18,30). A previous study demonstrated that TIRC7 plays an important regulatory function in both T and B cell responses (19).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of Th cells via f low cytometr y was performed as previously described (14). Anti-CD3-FITC (cat.…”
Section: Construction Of Pgpu6-shtirc7 and Flag-ctla-4mentioning
confidence: 99%
“… 12 Overall, studies have characterized the clinical relevance of type 1 immune reactions in patients with acquired AA, and the corresponding therapeutic strategy has begun to take advantage of the down-regulation in Th1 cells to reverse the loss of HSCs. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%